Analisis Kesesuaian Mekanisme Perolehan Koin Shopee dan Kupon Bonus TikTok Shop Dalam Perspektif Akad Ju’alah Berdasarkan Fatwa DSN-MUI - Khoirunisa Agustina; Istianah; Makhrus; Encep Saepudin (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2026)
The development of e-commerce has encouraged the emergence of digital reward systems given to users based on certain activities. The Shopee and TikTok Shop platforms have developed rewards to increase user participation, but have not been widely studied from the perspective of the ju'alah contract based on the DSN-MUI Fatwa No. 62/2007. This study aims to analyze the mechanism of obtaining Shopee Coins and TikTok Shop Bonus Coupons from the perspective of the DSN-MUI fatwa on the ju'alah contract. The method used is qualitative research with a normative juridical approach through documentation studies and non-participant observation. The results show that although the digital reward mechanism in e-commerce has similarities with the ju'alah contract, especially in providing rewards for an activity, its implementation is not fully in line with the principles set out in the fatwa. In Shopee Coins, the conformity is seen in the product purchase feature and daily missions that have clear provisions, but in the game feature there are still elements of uncertainty in rewards (jahalah) and certain conditions that can reduce the clarity of the contract. Meanwhile, the TikTok Shop Bonus Coupon tends to align more closely with the principles of ju'alah because it offers clearly defined rewards from the outset. This study concludes that digital reward practices in e-commerce face challenges in fully implementing the ju'alah contract, particularly due to the dynamic and gamificationbased nature of the system. Therefore, developing a more adaptive understanding of Islamic jurisprudence (fiqh) is necessary to accommodate digital innovation without neglecting sharia principles.